PERAN CITRA MEREK SEBAGAI MEDIASI ELECTRONIC WORD OF MOUTH TERHADAP MINAT BELI SKINCARE AVOSKIN - Abadi, Andhika Pangestu; Fitri, Raisa (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
The purpose of this study is to identify the effect of Avoskin Instagram Skincare followers' purchase intention by using electronic word of mouth to act as an independent variable with brand image as a mediating variable. This study uses followers of Avoskin's Instagram social media account as a population, aged at least 18 years. Non-probability sampling and purposive sampling methods were used as sampling techniques with a total sample of 170 respondents. Data collection was carried out through online questionnaires as a survey method. SEM (Structural Equation Model) is used as a data analysis method with the PLS technique using the SmartPLS software. The findings obtained by the researchers indicate that the application of electronic word of mouth on the Avoskin online social platform has a positive effect on the purchase intention Avoskin skincare products. Furthermore, brand image is able to be a positive mediation on the correlation of electronic word of mouth on purchase intention.